Fungal appendicitis: a case series and review of the literature. - Noppadol Larbcharoensub (2018)
Appendicitis is a condition characterized by inflammation of the vermiform appendix, which is commonly caused by bacterial infections and rarely caused by fungal organisms. In the present study, we reviewed the prevalence, clinicopathological features, and therapeutic management of fungal appendicitis. During July 2010 to June 2011, the pathology of 262 resected vermiform appendices was reviewed. Fungal appendicitis occurred in 1.15%, including two cases of Candida spp and one case of Aspergillus spp infection. All patients were immunocompromised and presented with the classical signs and symptoms of appendicitis with the onset of illness less than two days. They were considered for acute appendicitis and underwent appendectomy. The histopathology of the resected vermiform appendix showed fungal organisms with suppurative inflammation and secondary periappendiceal peritonitis. The curative treatment was presented in 1-out-of-3 cases. One patient was alive during a follow-up of eight months. Two patients died, and an autopsy was performed in one case. Although fungal appendicitis was uncommon, the disease might occur among immunosuppressed patients who have developed classical signs and symptoms of appendicitis. Early diagnosis and prompt surgery with medical treatment are associated with a survival advantage.